2014
DOI: 10.1038/npp.2014.195
|View full text |Cite
|
Sign up to set email alerts
|

The Dopamine Stabilizer (−)-OSU6162 Occupies a Subpopulation of Striatal Dopamine D2/D3 Receptors: An [11C]Raclopride PET Study in Healthy Human Subjects

Abstract: (-)-OSU6162 is a dopamine stabilizer that can counteract both hyperdopaminergic and hypodopaminergic states. In this study, D2/D3 receptor occupancy of (-)-OSU6162 in the human brain was investigated using positron emission tomography (PET). Twelve male healthy volunteers underwent [(11)C]raclopride PET scanning before and 1 h after a single oral dose of (-)-OSU6162 (15-90 mg). Blood samples for determination of (-)-OSU6162 and prolactin plasma levels were collected at Tmax. Parametric images of [(11)C]raclopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Human occupancy data for pridopidine have not yet been reported, but a recent 11 C-raclopride study (Tolboom et al 2015 ) examined D 2 R occupancy by (−)-OSU6162 and observed a 2 to 33 % occupancy in human subjects that received doses ranging from 15 to 90 mg (between 0.14 and 1.25 mg/kg). Since the dose-occupancy curve appeared to level off at 40 %, the authors suggested that (−)-OSU6162 selectively occupies a subset of striatal D 2 Rs, a property which could potentially account for some of the characteristics of dopamine stabilizers.…”
Section: Discussionmentioning
confidence: 99%
“…Human occupancy data for pridopidine have not yet been reported, but a recent 11 C-raclopride study (Tolboom et al 2015 ) examined D 2 R occupancy by (−)-OSU6162 and observed a 2 to 33 % occupancy in human subjects that received doses ranging from 15 to 90 mg (between 0.14 and 1.25 mg/kg). Since the dose-occupancy curve appeared to level off at 40 %, the authors suggested that (−)-OSU6162 selectively occupies a subset of striatal D 2 Rs, a property which could potentially account for some of the characteristics of dopamine stabilizers.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate adherence, samples for measurements of (−)‐OSU6162 plasma concentrations were drawn on all patients at days 14 and 84 about 90 minutes after medication intake in the morning. Plasma concentrations of (−)‐OSU6162 were determined by high performance liquid chromatography/tandem mass spectrometry as described previously …”
Section: Methodsmentioning
confidence: 99%
“…If there is indeed an increase in tonic DA signalling in morbid obesity, would this result in the recruitment of extra-synaptic DA receptors? It appears at least from a recent PET study on humans that [ 11 C]raclopride binds to an appreciable level of extra-synaptic D2Rs (52). This raises the tantalizing possibility that the findings from Wang et al are a result of decreased occupancy of extrasynaptic D2Rs as a consequence of increased tonic DA signalling.…”
Section: Obesity Reviewsmentioning
confidence: 99%